THE EFFECT OF USING CUBING TECHNIQUE TOWARD WRITING SKILL OF ANALYTICAL EXPOSITION TEXT OF THE SECOND YEARS STUDENTS AT MTS FATHUL ANWAR SUKA MAJU - -, Zuraida; Rasyidah, Ummi; -, Eripuddin (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2015)
The purpose of the research was to find out the effect of cubing technique in studentsâwriting skill of analytical exposition text. The findings showed that there is significant effectbetween teaching analyrical exposition text with using cubing technique. It can be seen of thevalue of t0(thitung) = 7,183 is bigger than tt(ttable) with significance 5%= 2,00 by using cubingtechnique..